Penerapan Biaya Denda Pada Akad Sewa Menyewa dalam Persepektif Hukum Islam - Nurhadi (Study Program Ekonomi Syari'ah, Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2015)
Application of penalty charges made if the tenant negligent and less cautious in keeping the rented goods, for the negligence of the tenant in the return of the rented goods in terapakan charge a fine per-hour delay, the calculation of 10% of the price in your rental price, while for severe damage to the rented goods rental apply in the calculation of the cost of repairs to both parties to the rental agreement. Meanwhile, according to Islamic law are allowed to apply the cost of fines provided that the parties of charge fines actually afford to pay, and if not then it should not be of charge fines because reviling one of the parties.